2021
DOI: 10.3390/ijms222212361
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Dietary Vitamin D Levels on Olanzapine-Induced Metabolic Side Effects: Focus on the Endocannabinoidome-Gut Microbiome Axis

Abstract: Vitamin D deficiency is associated with poor mental health and dysmetabolism. Several metabolic abnormalities are associated with psychotic diseases, which can be compounded by atypical antipsychotics that induce weight gain and insulin resistance. These side-effects may be affected by vitamin D levels. The gut microbiota and endocannabinoidome (eCBome) are significant regulators of both metabolism and mental health, but their role in the development of atypical antipsychotic drug metabolic side-effects and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 99 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…The probiotic Bacteroides has also been shown to produce the endothelin-like molecule N-acyl-3-hydroxypalmitoyl-glycine (commendamide) ( Cohen et al, 2015 ; Lynch et al, 2017 ). Furthermore, olanzapine-induced metabolic effects have been shown to be dependent on the endogenous cannabinoid system ( Abolghasemi et al, 2021 ). Everard et al showed that treating obese mice with A. muciniphila increased intestinal 2-oleoylglycerol (2-OG), 2-arachidonoylglycerol (2-AG) and 2-palmitoylglycerol (2-PG) levels ( Everard et al, 2013 ).…”
Section: Mechanisms Of Sga-induced Disorders Of Lipid Metabolism Medi...mentioning
confidence: 99%
“…The probiotic Bacteroides has also been shown to produce the endothelin-like molecule N-acyl-3-hydroxypalmitoyl-glycine (commendamide) ( Cohen et al, 2015 ; Lynch et al, 2017 ). Furthermore, olanzapine-induced metabolic effects have been shown to be dependent on the endogenous cannabinoid system ( Abolghasemi et al, 2021 ). Everard et al showed that treating obese mice with A. muciniphila increased intestinal 2-oleoylglycerol (2-OG), 2-arachidonoylglycerol (2-AG) and 2-palmitoylglycerol (2-PG) levels ( Everard et al, 2013 ).…”
Section: Mechanisms Of Sga-induced Disorders Of Lipid Metabolism Medi...mentioning
confidence: 99%
“…Various studies find that healthy diets have a positive effect on the gut microbiome. The diversity of the gut microbiome can be affected by diets, which may influence one's mental health [17,36], leading to potential improvements in mental health [15][16][17][18][19][20][21][22][23][24][25][26][27]29]. A healthy diet commonly refers to the consumption of vegetables, fruits, fish, and whole-diet interventions instead of only examining individual nutrients or foods.…”
Section: Positive Effects Of Diet On the Gut Microbiome That Potentia...mentioning
confidence: 99%
“…Positive effects: Other specific foods: Dietary vitamin D, unpasteurized milk, foods with a low omega-3 to omega-6 ratio, and Xiao Yan San [15,19,27,28], may also have a positive effect on the gut microbiome. Consuming a sufficient amount of vitamin D helps to regulate the gut microbiome and benefit gut health [53].…”
Section: Positive Effects: Mediterranean Style Dietmentioning
confidence: 99%
See 1 more Smart Citation